2018
DOI: 10.1128/jvi.01969-17
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD63 Bridges Autophagic and Endosomal Processes To Regulate Exosomal Secretion and Intracellular Signaling of Epstein-Barr Virus LMP1

Abstract: The tetraspanin protein CD63 has been recently described as a key factor in extracellular vesicle (EV) production and endosomal cargo sorting. In the context of Epstein-Barr virus (EBV) infection, CD63 is required for the efficient packaging of the major viral oncoprotein latent membrane protein 1 (LMP1) into exosomes and other EV populations and acts as a negative regulator of LMP1 intracellular signaling. Accumulating evidence has also pointed to intersections of the endosomal and autophagy pathways in maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 96 publications
4
89
0
Order By: Relevance
“…Since LMP1 has previously been shown to increase EV production, we wondered whether TM5-6 similarly enhances EV levels. Nanoparticle tracking analysis of cells transfected with LMP1 confirmed previous findings of elevated EV production (P Ͻ 0.05) (28,57); however, expression of TM5-6 produced levels of particles comparable to those of control GFP-transfected cells (P ϭ 0.16) ( Fig. 7D).…”
Section: Figsupporting
confidence: 86%
“…Since LMP1 has previously been shown to increase EV production, we wondered whether TM5-6 similarly enhances EV levels. Nanoparticle tracking analysis of cells transfected with LMP1 confirmed previous findings of elevated EV production (P Ͻ 0.05) (28,57); however, expression of TM5-6 produced levels of particles comparable to those of control GFP-transfected cells (P ϭ 0.16) ( Fig. 7D).…”
Section: Figsupporting
confidence: 86%
“…35,36 Previous studies indicated that CD63 is a critical player in shuttling LMP1 into EVs or exosomes. [17][18][19] However, the molecular mechanism by which LMP1 promotes EV secretion is not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt and MAPK/ERK signaling pathways to promote malignant cell growth, invasion, and metastasis. 15,16 CD63 is a critical player in LMP1 exosomal trafficking and LMP1-mediated enhancement of EV production, [17][18][19] and it has been found that C-terminal farnesylation of UCH-L1 is also one of the mechanisms by which LMP1 is sorted to EVs. 20 Therefore, LMP1 cannot only be loaded in EVs, but might also be involved in the regulation of EV secretion.…”
Section: Furthermore Transmission Of Lmp1-evs To Recipient Cells Actmentioning
confidence: 99%
“…Based on the origin of EVs a number of proteins are well established as markers. Among these are the tetraspanins characterized by four membrane spanning helices, including most notably CD63 [27][28][29][30][31]. CD63 is predominantly localized to the intraluminal vesicles (ILVs) of late endosomes and MVBs and is thus enriched on exosomes [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Among these are the tetraspanins characterized by four membrane spanning helices, including most notably CD63 [27][28][29][30][31]. CD63 is predominantly localized to the intraluminal vesicles (ILVs) of late endosomes and MVBs and is thus enriched on exosomes [31][32][33]. Cytoplasmic proteins including members of the endosomal sorting complex required for transport (ESCRT) machinery, syntenin, and certain chaperones are also enriched in EVs [32,34].…”
Section: Introductionmentioning
confidence: 99%